The evolution of reproductive mode in the Carassius auratus complex - Reem Al-Haidose (23752881) (2025)
Freshwater fish of the genus Carassius are widely distributed across Asia, Europe, and Australia. This includes the Carassius auratus complex, a phylogenetically diverse species group with uncertain taxonomy. The C. auratus complex is native to Asia but has been introduced to non-native habitats worldwide. It comprises both sexually reproducing diploid individuals and polyploid individuals that predominantly reproduce asexually through gynogenesis. The evolutionary relationships between these different reproductive modes, as well as the invasion history of the various lineages, are poorly understood. A phylogenetic approach using mitochondrial DNA (Cyt b sequence) in combination with six microsatellite markers was employed to investigate the invasion history of different lineages and reproductive modes and to explore the evolutionary relationships between them. The Cyt b analysis was based on sequences from 10 native populations in China and 35 invasive populations in Europe and Australia. Additionally, 1,427 individuals representing 93 populations from China, Europe, and Australia were genotyped at six microsatellite loci to determine their ploidy level and reproductive mode. Phylogenies of three nuclear genes were also used to test two hypotheses regarding the origin of triploid lineages: allopolyploidy and autopolyploidy. Our results suggest that the invasion of the C. auratus complex in Europe occurred through two routes, possibly driven by both historical and anthropogenic events. The microsatellite analysis revealed that 67.19% of individuals were triploids and 33.8% were diploids among the 1,427 individuals studied. Interestingly, most native populations consisted of a mix of diploids and triploids, with triploids predominating. In contrast, invasive populations exhibited considerable variation in reproductive modes, ranging from purely diploid to purely triploid and mixed populations. Additionally, diploids were dominant in older Eastern European populations, while triploids were dominant in more recently established Central European populations. Both mtDNA and microsatellite markers revealed no separation at the ploidy level, as alleles were shared by both diploid and triploid individuals, and sympatric diploids and triploids shared mtDNA haplotypes in seven highly diverged lineages and sublineages. Furthermore, the high genetic diversity observed in triploid forms may result from propagule vectors, which help mitigate the genetic bottleneck effects typically seen in successfully invasive species. The origin of gynogens could not be conclusively determined using nuclear DNA (Rag1 and S7 genes), as Rag1 analysis suggested an allopolyploid origin, while S7 analysis pointed to an autopolyploid origin. The C. auratus complex provides an ideal model for studying the reproductive traits of polyploid triploids, which holds significant value in animal genetics and reproductive biology. Other Information Conference information: 18th Edition of the Qatar University Life Sciences Symposium Bio-Environment: Advances and Innovations. (26 - 27 Nov 2025, Qatar University, Doha - Qatar) License: https://creativecommons.org/licenses/by/4.0/ See the conference information on the organizer's website: https://www.qu.edu.qa/en-us/conference/QULSS2025/Pages/default.aspx